2018
DOI: 10.1002/nme.5767
|View full text |Cite
|
Sign up to set email alerts
|

The discrete element method with deformable particles

Abstract: Summary This work presents a new original formulation of the discrete element method (DEM) with deformable cylindrical particles. Uniform stress and strain fields are assumed to be induced in the particles under the action of contact forces. Particle deformation obtained by strain integration is taken into account in the evaluation of interparticle contact forces. The deformability of a particle yields a nonlocal contact model, it leads to the formation of new contacts, it changes the distribution of contact f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
5
33
0
Order By: Relevance
“…As a consequence of this modification, the formation of new contacts has been induced and a nonlocal contact model with mutual dependence of the contacts experienced by the particles has been obtained. A similar effect, the nonlocal contact model and formation of new contacts, has been obtained by Rojek et al assuming the particles are deformed globally under the uniform internal stress. It has also been shown that the deformable DEM (DDEM) developed in the work of Rojek et al broadens the range of the macroscopic Poisson's ratio in comparison to the values achievable in the standard DEM (SDEM).…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…As a consequence of this modification, the formation of new contacts has been induced and a nonlocal contact model with mutual dependence of the contacts experienced by the particles has been obtained. A similar effect, the nonlocal contact model and formation of new contacts, has been obtained by Rojek et al assuming the particles are deformed globally under the uniform internal stress. It has also been shown that the deformable DEM (DDEM) developed in the work of Rojek et al broadens the range of the macroscopic Poisson's ratio in comparison to the values achievable in the standard DEM (SDEM).…”
Section: Introductionsupporting
confidence: 70%
“…The normal force f n combines with the tangential contact force f T yielding the total contact force between the considered pair of particles f c expressed as boldfc=fnboldnc+boldfT0.1em. In this work, it is assumed that the tangential contact force is unaffected by the particle deformation, and it is calculated taking any model used in the SDEM. In general formulation, other contact force components such as damping force can also be included in the contact interaction model (cf the work of Rojek et al). Here, in order to keep the simplicity of the analyzed formulation, we will focus on the evaluation of elastic normal force given by Equation .…”
Section: General Framework Of the Ddemmentioning
confidence: 99%
See 3 more Smart Citations